Preoperative MRI for predicting pathological changes associated with surgical difficulty during laparoscopic cholecystectomy for acute cholecystitis. Issue 6 (7th September 2020) - Omiya, K; Hiramatsu, K; Kato, T; Shibata, Y; Yoshihara, M; Aoba, T; Arimoto, A; Ito, A
Abstract: Background: Severe inflammation with necrosis and fibrosis of the gallbladder in acute cholecystitis increases operative difficulty during laparoscopic cholecystectomy. This study aimed to assess the use of preoperative MRI in predicting pathological changes of the gallbladder associated with surgical difficulty. Methods: Patients who underwent both preoperative MRI and early cholecystectomy for acute cholecystitis between 2012 and 2018 were identified retrospectively. On the basis of the layered pattern of the gallbladder wall on MRI, patients were classified into three groups: high signal intensity (HSI), intermediate signal intensity (ISI), and low signal intensity (LSI). The endpoint was the presence of pathological changes of the gallbladder associated with surgical difficulty, such as necrosis, abscess formation and fibrosis. Results: Of 229 eligible patients, pathological changes associated with surgical difficulty were found in 17 (27 per cent) of 62 patients in the HSI group, 84 (85 per cent) of 99 patients in the ISI group, and 66 (97 per cent) of 68 patients in the LSI group ( P < 0·001). For detecting these changes, intermediate to low signal intensity of the gallbladder wall had a sensitivity of 90 (95 per cent c.i. 84 to 94) per cent, specificity of 73 (60 to 83) per cent and accuracy of 85 (80 to 90) per cent. Conclusion: Preoperative MRI predicted pathological changes associated with surgical difficulty during laparoscopic cholecystectomy for acute cholecystitis. Graphical Abstract: Variations in the layered pattern of the gallbladder wall on MRI were significantly associated with fibrosis and necrosis of the gallbladder wall in acute cholecystitis. Intermediate to low signal intensity of the gallbladder wall on MRI had a sensitivity of 90 per cent and a specificity of 73 per cent for predicting pathological changes in the gallbladder wall associated with surgical difficulty during laparoscopic cholecystectomy for acute cholecystitis. The results indicate that MRI could be a novel method of predicting surgical difficulty in laparoscopic cholecystectomy. MRI could possilby predict surgical difficulty of cholecystectomy.